Decisive factors for the quality of life of patients who survived an ictus - Yoany Mesa Barrera; Tania Elena Hernández Rodríguez; Yanneris Parada Barroso (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: Cerebrovascular diseases (CVD) are a cause of affectedness related to quality of life (QL), and disability; the factors related to an affectedness of the quality of life vary from one study to another, considering the use of tools to measure the quality of life (scales) adapted to particular geographic areas.  Objective:To determine those factors that influence the most in the affectedness related to the quality of life of patients who have suffered an ictus, through the results presented in the literature on this topic. Material and methods:A total of 53 sources of information were consulted, among them 47 articles from scientific journals, 2 PhD thesis, and statistical reports. Also, it was possible to have access to the main managers of computing networks. Development:Concepts of the health-related quality of life of those patients who survived an ictus were considered, as well as the factors associated with their affectedness, the scales for quality of life assessment of patients with ictus, and the importance to conduct studies with a more integral approach. Conclusions:Independently of the existence of a group of common variables, which are essential in any study related to the quality of life of patients who survive an ictus, each research group has to keep in mind those elements that adapt most to the objectives in order to begin a research process. Keywords:cerebrovascular accident (CVA), quality of life, caregivers, disability, lifestyle, outcomes in the ictus, excess.